Organic solar cells materials, devices, interfaces, and modeling - Qiao, Qiquan 1975- (Devices, circuits, and systems, 2015)
This book discusses cutting-edge photovoltaic materials, devices, and systems. Divided into three sections, the text first provides an overall background of solar energy utilization devices and systems, considering the current economic and ecologic concerns over different energy sources. It then describes novel solar cell materials and devices, including organic, inorganic, and organic/inorganic hybrid solar cells as well as single- and multi-junction devices. Lastly, the book explores solar cell device physics and characterization, conveying the importance of harnessing reliable alternative energy sources